TUTORIALES VIRTUALES Y SU APORTE EN EL APRENDIZAJE DE LOS ESTUDIANTES DE EDUCACIÓN BÁSICA SUPERIOR DE LA UNIDAD EDUCATIVA FRANCISCO MARTINEZ AGUIRRE DEL CANTÔN VINCES, PERIODOACADÊMICO ABRIL – AGOSTO 2024. - VERA VEAS ÁNGELO HUMBERTO (2024)
The objective of the research was to analyze the methodological strategies in virtual tutoring for the teaching and learning process of students in the eighth, ninth and tenth year of basic education at the “Dr. Francisco Martínez Aguirre”, Vinces Canton, Los Ríos Province. As well as identifying the teaching strategies applied in virtual tutoring by teachers and determining the management of virtual tutoring for the effectiveness of student learning through the application of the instrument in the surveys in this research to students and teachers. The methodology that was applied had a quantitative and qualitative approach of an exploratory and descriptive type; The research was applied to a population of 7 teachers and 235 students, taking as a sample 147 students of higher basic education.